2022
DOI: 10.3171/2021.4.jns2169
|View full text |Cite
|
Sign up to set email alerts
|

Triceps and cutaneous radial nerve branches investigated via an axillary anterior arm approach: new findings in a fresh-cadaver anatomical study

Abstract: OBJECTIVE The authors sought to describe the anatomy of the radial nerve and its branches when exposed through an axillary anterior arm approach. METHODS Bilateral upper limbs of 10 fresh cadavers were dissected after dyed latex was injected into the axillary artery. RESULTS Via the anterior arm approach, all triceps muscle heads could be dissected and individualized. The radial nerve overlaid the latissimus dorsi tendon, bounded by the axillar artery on its superior surface, then passed around the humerus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Surgery was conducted through an axillary-arm incision (Bertelli et al, 2011(Bertelli et al, , 2021. The musculocutaneous nerve was observed to have a normal path, piercing the coracobrachialis muscle.…”
Section: Triceps Paralysis With Intact Distal Radial Nerve Function I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery was conducted through an axillary-arm incision (Bertelli et al, 2011(Bertelli et al, , 2021. The musculocutaneous nerve was observed to have a normal path, piercing the coracobrachialis muscle.…”
Section: Triceps Paralysis With Intact Distal Radial Nerve Function I...mentioning
confidence: 99%
“…Under electrical stimulation, branches to the biceps and brachialis muscles elicited full contraction. The triceps motor branches were further dissected along the anterior portion of the radial nerve (Bertelli et al., 2021) and we identified a neuroma-in-continuity about 2.5 cm over the latissimus dorsi tendon (Figure 1). The neuroma was removed and sent for histological evaluation.…”
mentioning
confidence: 99%
“…The LHT is typically the first motor branch off of the RN followed by the upper branch of the medial head. 4,5 The posterior cutaneous branch of the arm (PCB) supplies the posterior upper arm and is most often proximal to the LHT branch but may share a common trunk. The LHT is an ideal recipient because it is the largest of the triceps heads, innervated by a single cohesive branch, which enters the proximal muscle belly just distal to the LAT tendon.…”
Section: Surgical Anatomymentioning
confidence: 99%
“…Anatomic studies have shown that the MH has a separate insertion deep to the common insertion of LH and LaH on the olecranon. 19 The MH has a muscular insertion, with a smaller tendinous portion that can be identified deep to the conjoined tendons of the LH and LaH. 24 The triceps receives its innervation from the radial nerve, one of two terminal branches of the posterior cord of the brachial plexus, which is formed by the C5 to T1 cervical roots.…”
Section: Anatomymentioning
confidence: 99%
“…17 The anatomy of the radial nerve has been well-defined; however, a peripheral nerve-based procedure to address triceps spasticity has not been reported. [18][19][20][21][22][23] Given the course of the radial nerve, broad branching pattern, and variable anatomy, an entirely nerve-based procedure would require extensive exposure in the posterior arm. As such, this study aims to present our surgical technique for treating triceps spasticity, which involves combining triceps tendon lengthening of the long (LA) and lateral (LaH) heads with HSN of the medial head (MH) of the triceps through a targeted distally based incision.…”
mentioning
confidence: 99%